Watch her fall - Kelly, Erin (Hodder & Stoughton, 2021)
"Ava Kirilova has reached the very top of her profession. After years and years of hard graft, pain and sacrifice as part of the London Russian Ballet Company, allowing nothing else to distract her, she is finally the poster girl for Swan Lake. Even Mr K - her father, and the intense, terrifying director of the company - can find no fault. Ava has pushed herself ahead of countless other talented, hardworking girls, and they are all watching her now. But there is someone who really wants to see Ava fall."--Publisher.